Strategi Konservasi dan Pengelolaan Rusa Timor (Rusa timorensis) dengan Model Integrated Adaptive Conservation Management (IACM) di Pulau Lombok - Abdul Kadir Alaydrus; Pahmi Husain (MASALIQ, 2026)
The Timor deer (Rusa timorensis) is a herbivorous mammal that plays an important role in maintaining the balance of dry tropical forest ecosystems in Indonesia. However, its population on Lombok Island continues to face pressure from deforestation, habitat fragmentation and degradation, illegal hunting, and increasing human–wildlife conflict. Although various studies have addressed Timor deer conservation, the available research remains partial and has not produced a comprehensive synthesis as a basis for adaptive management. This study aims to synthesize developments in research on the conservation and management of Timor deer on Lombok Island through a scoping review approach. The review was conducted based on the PRISMA-ScR guidelines by searching the Scopus, Web of Science, ScienceDirect, SpringerLink, Google Scholar, Garuda, and Neliti databases. Of the 285 articles identified, 38 publications met the inclusion criteria and were analyzed qualitatively and descriptively using thematic analysis. The synthesis results show that research on Timor deer remains dominated by studies of habitat distribution, population dynamics, and in situ conservation, whereas collaborative governance, conservation policies, and community participation have received limited attention. The main threats to the sustainability of Timor deer populations include land-use conversion, habitat fragmentation, illegal hunting, declining forage quality, and weak management of conservation areas. Based on these findings, this study proposes the Integrated Adaptive Conservation Management (IACM) model, which integrates in situ and ex situ conservation, collaborative governance, and the use of conservation technology as an adaptive management strategy. This model provides a conceptual contribution to the development of wildlife management and may serve as a scientific basis for formulating evidence-based conservation policies to support the sustainability of Timor deer populations and biodiversity management on Lombok Island.